G73 A survey of uk paediatricians' awareness and enquiry regarding adverse childhood experiences (aces). (12th March 2018) - Venkatesan, P; Akindolie, O
Abstract : Aims: The publication of the pioneering Adverse Childhood Experiences (ACEs) study, 1 has resulted in an increasing body of evidence demonstrating that exposure to ACEs has a significant impact on adult health outcomes. Our aim was to evaluate the level of awareness and enquiry regarding ACEs amongst paediatricians in clinical practice in the UK. Methods: An electronic questionnaire was distributed to a sample of hospital and community based paediatricians in practice in the UK. Details of the original ACE study were provided including the 10 ACEs: Abuse: Physical Emotional Sexual Neglect: Physical Emotional Household Member: Mental illness Substance Misuse Incarceration Maternal Domestic Violence Parental Divorce or Separation Questions were subsequently posed regarding the current level of routine enquiry and management of ACEs in paediatric clinical consultations. Results: The survey resulted in 74 completed questionnaires. Prior to this survey, 50% of the respondents were not familiar with the findings of the original ACEs study whilst 16.7% reported being very familiar with the findings. Enquiry related to ACEs in paediatric clinical consultations (table 1): Conclusion: Whilst knowledge of the ACEs study appears to be relatively low amongst the sampled group of UK paediatricians, it is reassuring that enquiry related to specific ACEs is already embedded in clinical practice. This is supported by the presence of an excellent and established range of allied services available for onward referral and definitive management. The American Academy of Paediatrics (AAP) has published a position statement supporting routine screening for ACEs in the USA. 2 This has resulted in a gathering of momentum with an ACE focussed approach to paediatrics supported by the National Paediatric Practice Community (NPPC). 3 The findings of this survey represent a significant opportunity. A compelling case is made for child advocacy and an evidence base for sustained investment in all allied services which positively impact on ACEs. The future health of the nation rests on our collective response to the findings of the ACEs study. References: . Felitti VJ, Anda RF, Nordenberg D, et al. Relationship of child-hood abuse and household dysfunction to many of the leading causes of death in adults: The Adverse Childhood Experiences (ACE) Study. American Journal of Preventive Medicine14:245–258. . Andrew S Garner, Jack P Shonkoff, Benjamin S Siegel, Mary I Dobbins, Marian F Earls, Andrew S Garner, Laura McGuinn, John Pascoe, David L Wood. Early childhood adversity, toxic stress, and the role of the paediatrician: Translating developmental science into lifelong health. Paediatrics2012;129:e224–e231. . http://nppcaces.org [Accessed: 21st October 2017].